High pressure processing of European sea bass (Dicentrarchus labrax) fillets and tools for flesh quality and shelf life monitoring. (December 2019) - Tsironi, Theofania; Anjos, Liliana; Pinto, Patricia I.S.; Dimopoulos, George; Santos, Soraia; Santa, Cátia; Manadas, Bruno; Canario, Adelino; Taoukis, Petros; Power, Deborah
Abstract: The effects of high pressure (HP:600 MPa, 5 min, 25 °C) on European sea bass fillets were investigated using microbiological, physicochemical and sensory indices, and "omics" technologies. HPP led to more than a 5 log(cfu/g) reduction in initial bacterial total viable counts and altered the bacterial microbiome, reducing the proportion of food spoilage genera. Lightness and hardness of the fish flesh significantly increased after HPP and were associated with modified muscle tissue histology, with fibers appearing fused and more compact in comparison to the unprocessed control. Sensory evaluation (based on a lower limit of 5 for overall acceptability scoring) indicated a shelf life of 11 days for untreated control samples and 2 months for the HP-treated fillets. Quantitative SWATH proteomics revealed 281 proteins that had modified levels between control and HP-processed fish flesh. The metagenomics and proteomics provided detailed insight into how the change in HP-processed sea bass fillets is linked to the modifications in the microbiome and proteome. Highlights: High pressure processing (HPP) prolonged sea bass fillet shelf life for approx. 2 months at 2 °C. HPP reduced the initial microbial load and the proportion of food spoilage genera. HPP fillets had increased lightness and hardness and more compact muscle fibers. 281 proteins had modified levels between control and HPP-processed fish flesh. Integration of classical/novel technologies may be used to improve fish fillet quality.